Updates to Concepts on Phreatomagmatic Maar-Diatremes and Their Pyroclastic Deposits - Valentine, Greg A.; White, James D. L.; Ross, Pierre-Simon; Graettinger, Alison H.; Sonder, Ingo (Frontiers in Earth Science, 2017)
Recent work is changing our understanding of phreatomagmatic maar-diatreme eruptions and resulting deposits. In previous models, explosions were often inferred to take place only at the base of a diatreme, with progressive downward migration due to a cone of depression in the host aquifer. However, diatremes themselves contain much water that is heterogeneously distributed, and field evidence supports the existence of explosion sites at many vertical and lateral locations within them. Crater sizes have been used to estimate explosion energies, but this only works for single-explosion craters where the depth of explosion is independently known, and has limited value for multi-explosion maar-diatremes. Deep-seated lithic clasts in tephra ring beds have been taken to indicate the depth of the explosion that produced that bed. However, only relatively shallow explosions actually vent to the surface, and deep-seated lithics are gradually brought to shallow depths through step-wise mixing of multiple subsurface explosions. Grain-size of tephra-ring deposits is often inferred to indicate fragmentation efficiency. However, other factors strongly influence deposit grain size, including the scaled depth of an explosion and the interaction of an erupting jet with topography around a vent (e.g., crater), along with long recognized effects of mechanical properties of host rocks and recycling within the vent/diatreme. These insights provide a foundation for future research into this important volcano type.